Contrasting mental health correlates of physical and sexual abuse-related shame. Issue 2 (4th May 2018) - Ellenbogen, Stephen; Colin-Vezina, Delphine; Sinha, Vandna; Chabot, Martin; Wells, Shauna J R
Abstract : Objective: This study represents an initial attempt to contrast behavioural and mental health correlates of shame as a result of physical abuse (PA) and sexual abuse (SA). Because they are distinctive forms of injury, it is possible that corollary shame from these injuries follows unique trajectories and ultimately results in different health challenges. Method: Self-report data from a survey on the health of youth receiving protective services for reasons of PA and SA was used. It included standardised measures, such as the Childhood Trauma Questionnaire, Trauma Symptoms Checklist for Children, the Brief Symptoms Inventory, the Rutgers Alcohol Problem Index, and the South Oaks Gambling Screen. New measures of abuse-related shame, maltreatment, and substance use were also employed. Linear regression analyses were performed to determine whether level of shame was linked to mental health and behaviour issues, after controlling for level of abuse. Results: Results were similar for shame as a result of PA and SA victimisation. After accounting for shared variance with abuse severity, both measures were linked to a full spectrum of mental health issues, such as depression (SA r 2 = 0.30, PA r 2 = 0.28), anxiety (SA r 2 = 0.27, PA r 2 = 0.20), post-traumatic stress (SA r 2 = 0.26, PA r 2 = 0.19), interpersonal sensitivity (SA r 2 = 0.17, PA r 2 = 0.22), and psychoticism (SA r 2 = 0.19, PA r 2 = 0.20), but not to gambling or substance use problems. PA-related shame was associated with suicidality ( r 2 = 0.05). Conclusions: Keeping in mind that this was largely a cross-sectional study and that causality cannot be inferred, the results seem to indicate that youth suffering from abuse-related shame are particularly vulnerable to mental health problems, but not to efforts to numb their problematic thoughts and feelings through gambling and substance use. Shame could serve as an early indicator of which child protection recipients are most in need of preventive efforts.